Cost efficiency measurement of leasing companies with SFA and DEA approach - Baten, Md Azizul; Hasan, A. H. M. Saidul (AENSI Publisher, 2014)
Nowadays the leasing industry is a successful industry in economic conditions, but there are few studies that deal with the assessment of leasing companies' efficiency in Bangladesh. Previous research for leasing company's' efficiency measurement usually adopts either DEA or SFA method, but not both of them. Therefore, this paper is aimed to measure the cost efficiencies of 15 leasing companies from 2002 to 2008 by applying both SFA and DEA models with four inputs and two outputs.The results suggest that leasing companies have generally less experience in the allocation of resources and in the improvement of cost efficiency.The coefficients of Interest revenue and Non Interest revenue are found significant and positive effects on the cost efficiency of the leasing company in case of stochastic cost frontier model. The results of technical efficiency and allocative efficiency are combined to provide a measure of total cost efficiency in case of cost data envelopment analysis.The lowest cost efficiency (39.6%) for Union Capital Limited, and highest cost efficiency (89.7%) for International Leasing & Financial S.Ltd., is observed in case of cost data envelopment analysis.